Introspections from the Margins of Race and Gender - Doris A. Flowers; Ming-Yeh Lee; Vanessa Sheared; Colleen Aalsburg Wiessner (Adult Education Research Conference, 2007)
Race, as most social scientist would argue, is socially constructed, and from that premise there are those who would argue that since it is socially constructed, it isn’t real and therefore why do we even talk about it. However rather than going with that premise, we would argue that given that it is socially constructed, the fact that we are social beings and that we have been socialized to recognize the color of another’s skin, then it matters, and we need to talk about it.